Automatic in situ sensor based on K2S2O8 oxidation method for total phosphorus detection in marine water - Zhang, Yanmin; Chen, Shougang; Liu, Yan; Zou, Yan; Wang, Yang; Zhang, Shuwei; Kong, Xiangfeng; Gao, Yang; Gao, Nan (Frontiers in Marine Science, 2024)
Phosphorus is a key indicator for water quality management due to its role in eutrophication. The variety of phosphorus-containing substances necessitates highly sensitive detection of total phosphorus, particularly through automated methods, to ensure water safety. This study involved the independent development of a sensor featuring an automated in situ detection technique. Utilizing potassium persulfate high-temperature oxidation and phosphorus molybdenum blue spectrophotometry, total phosphorus was monitored in situ via sequential injection technology. Additionally, the detection process and reaction conditions of the sensor were optimized, and a temperature compensation algorithm and turbidity correction were applied to mitigate environmental factors. Under optimal conditions, the sensor demonstrated a detection limit of 1.9 µg/L with a range of 6.5–1000 µg/L in seawater, and 1.2 µg/L with a range of 4.1–2000 µg/L in freshwater. The digestion efficiency for five representative phosphorus-containing substances was found to range from 87.3% ± 1.7% to 103.1% ± 0.6%. Notably, the sensor was deployed for in situ operation at a marine experimental station and online at a river monitoring station. With its integration, low power consumption, and high precision, the sensor enabled long-term unattended monitoring, delivering accurate, stable, and reliable results.